THE URGENCY OF ISLAMIC RELIGIOUS EDUCATION IN REALIZING ADOLESCENT MENTAL HEALTH IN THE ERA OF SOCIAL MEDIA - A’yun, Qurroti; Surayyah, Firda (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The main purpose of the study is to provide a comprehensive explanation of how Islamic religious education can significantly improve the mental health of adolescents in the digital era. The researcher collected data for this study from various written sources using a literature approach. Descriptive analysis is the method used to analyze the data in the study, while documentation is a data collection method. The findings of this study show that Islamic religious education can have a great impact by helping adolescents develop strong faith values, habits of worship, gratitude, and a good attitude towards learning